Unilateral Contrast Neurotoxicity as a Stroke Mimic After Cerebral Angiogram. Issue 2 (13th September 2011) - Haussen, Diogo C.; Modir, Royya; Yavagal, Dileep R.
ABSTRACT Contrast neurotoxicity (CN) following exposure to iodinated contrast is uncommon, and usually presents as cortical blindness due to bilateral occipital lobe involvement. Unilateral cortical dysfunction due to CN could mimic an acute stroke and has been rarely described. We report the case of an 89‐year‐old female who developed a transient dense/complete left homonymous‐hemianopsia and left‐sided tactile extinction after undergoing a right internal carotid (ICA) artery rotational angiogram with a standard high‐volume iodinated contrast injection for 3D visualization a 6×4‐mm right posterior communicating artery aneurysm with a fetal posterior cerebral artery (PCA) incorporated in the neck. This was associated with transient fullness and loss of gray‐white matter differentiation in the right occipital and parietal lobes. The potential mechanism of CN in our case was the injection of a high volume of contrast in the ICA for the rotational angiogram. The presence of a right fetal PCA possibly allowed the contrast to reach the right occipital lobe. CN manifesting as an acute focal neurologic syndrome should be considered in the setting of recent iodinated contrast exposure.